Overcoming potential barriers to investigating and treating myxomatous mitral valve disease - Belshaw, Zoe (BMJ Publishing Group, 2018)
Achieving a diagnosis of mitral valve disease (MMVD) can be relatively straightforward. Persuading owners to investigate and treat, and then maintaining adherence to a therapeutic regimen can be significantly more challenging. While heart murmurs are most likely to be detected during the annual health check or booster consultation, recent evidence suggests this might not be an ideal time to discuss MMVD. This article reviews some of the potential barriers to owners following practitioners’ recommendations, and suggests some solutions.